IMPLIKASI KONFLIK DALAM NOVEL BISIKAN DARI LANGIT KARYA GALANG LUFITYANTO: PENDEKATAN STRUKTURAL - Risya Rizky Nurul Qur’ani (Bajang Institute, 2022)
This study aims to describe the implications or effects of the conflict on other elements of the novel Bisikan dari Langit by Galang Lufityanto. The research uses a structural approach based on A.Teeuw's theory, which is the integrity of a unit that is built from interconnected elements. The method used in this study is a qualitative method. The results of this study indicate that there is a strong influence of conflict on other elements, such as characterization elements, setting, theme, and mandate.Thus, the main purpose of the novel is revealed, which is to show the moral decline caused by different characters and the people around the characters that are found in every moment and environment of their lives. Although the story of each chapter is different, the existing conflicts have the same pattern of connection with the purpose and meaning of the novel.